Research on Plant Landscape in Urban Wilderness Space: A Case Study of Jiangyangfan Ecological Park in Hangzhou - Xiao, Yao; Liao, Yuanqi (International Journal of Natural Resources and Environmental Studies, 2024)
In recent years, with the acceleration of urbanization, the construction and management of urban wilderness space has become an important research field. The study of plantscape in urban wilderness space is one of the key points. Plant landscape is the core element of urban wilderness space, which plays an important role in improving urban environment and ecosystem service function. In this study, we chose Hangzhou Jiangyangfan Ecological Park as an example, and identified two main areas, the habitat island and the lake area, to be used as the research sites for plant species. The distribution of plant species, community structure, seasonal variation and spatial characteristics of these areas were studied and evaluated in detail. Based on the actual data collection, we will propose the following plant construction strategies: introduction of native species, creation of communities close to nature, use of temporal characteristics of plants, and the use of plants to shape the aesthetics of horticultural spaces.